Identification and classification of distinct surface markers of T regulatory cells - Wegrzyn, Agnieszka S.; Kedzierska, Anna E.; Obojski, Andrzej (Frontiers in Immunology, 2023)
Background: Regulatory T (Treg) cells have emerged as key players in the maintenance of immune homeostasis. Although significant progress has been made in recent years to define the Treg surface markers involved with or identifying their suppressive function, there remains much to be elucidated, and many questions persist. This study determined the expression of surface markers on human peripheral Treg cells and conventional T (Tconv) cells in a steady state and after activation to gain insight into their mechanism of action and more precisely characterize this regulatory population in humans. Methods: To screen Treg and Tconv cells, peripheral blood mononuclear cells (PBMCs) were isolated from volunteers, stained with a commercially available lyophilized antibody array comprising 371 surface antigens, and analyzed by flow cytometry. To compare Treg cells with activated Tconv cells, PBMCs were stimulated with PMA and further stained similar to freshly isolated cells. Results: Treg and Tconv cells were positive for 135 and 168 of the 371 antigens, respectively. Based on the frequency distribution, all of the most highly expressed markers identified were shared by both Treg and Tconv cells and participate in T cell activation, act as costimulatory and signaling molecules, or exhibit adhesion and migratory functions. Additionally, we identified several differences in marker expression between Treg and Tconv cells, with most found in the expression of co-stimulatory (ICOS, GITR, 4-1BB) and co-inhibitory (TIGIT, CTLA-4) molecules, as well as chemokine receptors (CXCR4, CXCR5, CCR4, CCR5, CCR7, CCR8, and CXCR7). Furthermore, post-activation expression of surface molecules identified molecules capable of discriminating Treg cells from activated Tconv cells (GITR, 4-1BB, TIGIT, CD120b, and CD39); however, almost all of these markers were also expressed in a small fraction of activated Tconv cells. Conclusions: These results offer insight into the biology of Tregs and contribute to their accurate identification and characterization in inflammatory diseases.